KESIAPAN PARA PELAKU UMKM DALAM MENYUSUN LAPORAN KEUANGAN BERDASARKAN STANDAR AKUNTANSI KEUANGAN ENTITAS MIKRO, KECIL DAN MENENGAH (SAK-EMKM) - Hj. Dewi Rejeki, SE., Ak., M.Si., CA. (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2020)
The research was conducted to find out in depth how the readiness of MSME actors in preparing financial reports based on SAK-EMKM. The emphasis is aimed at the extent to which these MSME actors understand the usefulness of financial reports that are prepared based on standard standards.This study uses a descriptive method with a qualitative approach through interviews, observation and documentation. The population in this study were several MSME players in the services, trade and manufacturing sectors, namely CV Dahkota in Cirebon (printing service business), Midio Restaurant in Jatiwaringin (food / culinary trading business), Arena Distro shop in Radin Inten (trading business). clothes), and Family Shoes in Bogor (a shoe manufacturing business).The results of this study found that there were some MSME actors unpreparedness, such as the financial statements presented only limited to income and expenditure, no recording of assets, inventories were only recorded based on physical calculations, and the recording was still based on cash basis